Unwanted Muslim immigrants, dignity, and drug dealing - Bucerius, Sandra M. (Oxford University Press, 2014)
This study builds on five years of ethnographic research with an all-male group of fifty-five Muslim second-generation immigrant drug dealers in Frankfurt, Germany, and examines the relationship among immigration, social exclusion, and the informal economy.